2009 First International Confernce on Advances in Databases, Knowledge, and Data Applications 2009
DOI: 10.1109/dbkda.2009.30
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and Integration of Databases Using Self-Organizing Map

Abstract: Abstract-With the growing computer networks, accessible data is becoming increasingly distributed. Understanding and integrating remote and unfamiliar data sources are important data management issues. In this paper, we propose to utilize self-organizing maps (SOM) clustering to aid with the visualization of similar columns, and integration of relational database tables and attributes based on the content. In order to accommodate heterogeneous data types found in relational databases, we extended the TFIDF mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The user of unsupervised clustering methods does not need to specify the expected number of clusters, while he must specify the expected number of clusters with the supervised clustering methods. It has already been demonstrated that HDM-UV works well with the unsupervised clustering method SOM [1]. We are aiming to demonstrate that the HDM-UV is applicable to algorithms other than SOM such as K-means.…”
Section: Processingmentioning
confidence: 99%
See 3 more Smart Citations
“…The user of unsupervised clustering methods does not need to specify the expected number of clusters, while he must specify the expected number of clusters with the supervised clustering methods. It has already been demonstrated that HDM-UV works well with the unsupervised clustering method SOM [1]. We are aiming to demonstrate that the HDM-UV is applicable to algorithms other than SOM such as K-means.…”
Section: Processingmentioning
confidence: 99%
“…It appears that when two data types, such as numerical and textual, are simultaneously processed by HDM, the use of unified vectorization (UV) leads to better convergent semantic clustering results [1]. In spite of good results, the development and the use of similar data weighting measures to represent these heterogeneous data types in a unified VSM matrix improves the clustering results [2].…”
Section: Pre-processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Where N j is elements of cluster j and N i is the number of elements of class i for class i and cluster j, N ij is the numbers of elements of class i in cluster j [12].…”
Section: F Measurementioning
confidence: 99%